1996
DOI: 10.1099/13500872-142-8-2263
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for different mannosylation processes involved in the association of  -1,2-linked oligomannosidic epitopes in Candida albicans mannan and phospholipomannan

Abstract: A monoclonal antibody specific for /?-1,2-linked oligomannosides was used to study the association of these residues with Candida albicans mannan and phospholipomannan (PLM) in relation to growth conditions and in mannan mutant strains. Double immunof luorescence assays performed on cells grown under standard conditions indicated a highly heterogeneous cell surface expression of these epitopes in comparison with the homogeneous expression of a-linked oligomannosidic epitopes. Growth in the presence of tunicamy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…This antigen, named phopholipomannan (17), is expressed only in C. albicans and C. tropicalis, which are the most pathogenic Candida species (25). PLM is synthesized by C. albicans including under growth conditions that prevent association of ␤-1,2-linked oligomannosides to phosphopeptidomannan (30). Recent experiments have shown that C. albicans, in contact with macrophages, shed large amounts of PLM, which triggers an intense phosphotyrosine kinase-dependent signaling pathway and the secretion of TNF-␣ (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This antigen, named phopholipomannan (17), is expressed only in C. albicans and C. tropicalis, which are the most pathogenic Candida species (25). PLM is synthesized by C. albicans including under growth conditions that prevent association of ␤-1,2-linked oligomannosides to phosphopeptidomannan (30). Recent experiments have shown that C. albicans, in contact with macrophages, shed large amounts of PLM, which triggers an intense phosphotyrosine kinase-dependent signaling pathway and the secretion of TNF-␣ (19).…”
Section: Discussionmentioning
confidence: 99%
“…3 H]Inositol-Preliminary characterization of C. albicans PLM was made through chloroform/methanol/water extraction procedure and Western blot analysis (30). When the same extraction procedure was applied to [ 3 H]mannose-labeled Fr.…”
Section: Tlc Analysis Of C Albicans Extracts Showed That Plm Correspmentioning
confidence: 99%
“…At the moment, the presence of ␤-1,2 oligomannosides has only been chemically proven in PPM and PLM (6,8). It is obvious from a large number of studies where blots were probed with anti-␤-1,2 oligomannoside monoclonal antibodies that, besides PPM and PLM, and depending on the growth conditions, ␤-1,2 oligomannoside epitopes are also expressed on a wide range of cell wall proteins where they generally co-localize with ␣-oligomannoside epitopes (7)(8)(9)26). In parallel, several C. albicans cell wall proteins have been shown to play an important role in pathogenesis or cell wall organization/remodeling.…”
Section: Fig 4 Mit1 Deletion Does Not Affect Cell Morphogenesismentioning
confidence: 99%
“…Western blots of C. albicans cell wall extracts show that ␤-oligomannoside epitopes co-localize with ␣-oligomannoside epitopes on mannosylated proteins (7) and are electively expressed on low molecular weight antigens that have been characterized as phospholipomannan (PLM) (8). Besides PPM, PLM is the second C. albicans molecule in which the presence of ␤-1,2 oligomannosides has been demonstrated chemically (9). PLM appears as a member of the cell membrane MIPC family from which it diverges by the addition of mannose and phosphate linking long linear chains of ␤-mannosides (10).…”
mentioning
confidence: 99%
“…It encompasses a large repertoire of antigenic oligomannose epitopes whose specificity is determined by the nature of the linkage between mannose residues and the length of the oligomannose chain (35). These epitopes are associated with a large variety of different yeast carrier molecules and may be species specific or shared by several species (3,(36)(37)(38). A clear-cut discrimination between ␣-and ␤-linked mannose residues is made by mammalian immune systems and endogenous lectins (11).…”
mentioning
confidence: 99%